Combined effects of refrigerant leakages and fouling on air-source heat pump performances in cooling mode. (5th March 2022) - Pelella, Francesco; Viscito, Luca; Mauro, Alfonso William
Highlights: Digital model of an electric air-to-air heat pump for domestic cooling. Fault Detection and Diagnosis tools for the identification of operating anomalies. Combined refrigerant leakages and heat exchanger fouling soft-faults analyzed. Impact of faults on thermodynamic cycle parameters and COP. Seasonal performances and TEWI for different climates and maintenance strategies. Abstract: For electric heat pump systems (EHP), soft faults such as refrigerant leakages and heat exchangers fouling can lead to significant performance degradations, which can remain unidentified for a long period. This paper, through a digital model, wants to simulate the cooling season behavior of a case study air-source heat pump for residential air-conditioning, analyzing the performance degradation in case of both standalone and simultaneous occurrence of soft faults. The study is carried-out in different scenarios of not planned and ordinary maintenance of the machine and in typical climate conditions of Naples, Miami and Shanghai. The impact of faults on seasonal performances (SCOP) and total equivalent warming impact (TEWI) has also been analyzed. Results show that refrigerant leakages can have an impact on system performance higher than 25%, whereas heat exchangers fouling can downgrade the efficiency of approximately 15%. It is also found that, for each climate condition, a different maintenance strategy can halve the cases with SCOP penalization higher than 10%. Since faults have not the same probability of occurrence, a smart monitoring and a fault detection system can be the solution to guarantee good performances avoiding at the same time excessive maintenance costs.